Knockdown of TRAF3IP2 suppresses the expression of VEGFA and the proliferation of keratinocytes and vascular endothelial cells. Issue 5 (May 2019) - Song, Yali; Chen, Lamei; Li, Yuanyuan; Lin, Qingxia; Liu, Wenmin; Zhang, Li
Abstract: Objective: To investigate the expression level of TRAF3IP2 in psoriasis lesion, and to explore the functional roles of TRAF3IP2 on proliferation, apoptosis, cytokine expression and secretion of both keratinocytes and vascular endothelial cells in vitro . Methods: The expression of TRAF3IP2 in skin samples of patients with psoriasis was analyzed by immunohistochemistry and qRT-PCR. To identify the effect of TRAF3IP2 knockdown on HaCaT and HUVEC cells, a plasmid vector expressing siRNA targeting TRAF3IP2 mRNA was designed and transfected into cells with Lipofectamine 2000. The levels of cytokines were identified using the ELISA Kits and qRT-PCR. Furthermore, cell proliferation, cell cycle and apoptosis were examined by using MTT, PI and Annexin V-FITC/7AAD assays, respectively. Furthermore, the expression of apoptosis-related proteins (Cleaved-Caspase 3, Caspase 3 and Bax) were detected by western blotting. Results: TRAF3IP2 was significantly upregulated in psoriasis lesion. TRAF3IP2 knockdown reduced the expression of vascular endothelial growth factor A (VEGFA) and the release of IL-6, and IL-8, but had no effect on IL-23 in both HaCaT and HUVEC cells. In addition, knockdown of TRAF3IP2 significantly inhibited cell proliferation through blocking the cell cycle in the G2/M phase. Moreover, knockdown of TRAF3IP2 increased the expression of Caspase 3, Cleaved-Caspase 3 and Bax, which was supported by the increased apoptosis of both HaCaT and HUVEC cells. Conclusion: Taken together, these results indicated that TRAF3IP2 might play a contributive role in the pathogenesis of psoriasis and may serve as a new target for the treatment of psoriasis. VEGF related pathways may be involved in the mechanism beneath.